When Would Driverless Vehicles Make Downtown Parking Unsustainable, and Where Would the Driverless Car Fleet Rest During the Day? - Robert A. Simons; David C. Feltman; Alexandra A. Malkin (Journal of Sustainable Real Estate, 2018)
In this study, we examine the sustainability of downtown parking in the likely advent of driverless vehicles (DVs). The confluence of driverless, electric, and fleet-owned cars is likely to influence personal car use choice of travel modes. We ask where driverless cars could be staged during the day. We review 21 available practitioner forecasts on DV adoption, and project that net demand for parking in downtown Cleveland would drop by 20%–66% by 2035. The servicing and staging needs for the expected “robotaxi” fleet of 1,300–4,300 vehicles could be accommodated by city-owned overflow parking by the lakefront airport or football sports stadium.